Antibacterial activities of the methanol extract, fractions and compounds from Elaeophorbia drupifera (Thonn.) Stapf. (Euphorbiaceae). Issue 1 (December 2017) - Voukeng, Igor; Nganou, Blaise; Sandjo, Louis; Celik, Ilhami; Beng, Veronique; Tane, Pierre; Kuete, Victor
Abstract Background Elaeophorbia drupifera (Thonn.) Stapf. (Euphorbiaceae) is used in Cameroonian folk medicine to treat several ailments including bacterial-related diseases such as skin infections. In this study, the methanol extract from the leaves (EDL), fractions (EDLa-d), sub-fractions EDLc1-7 and EDLc31-35 as well as isolated compounds were tested for their antimicrobial activities against a panel of Gram-negative and Gram-positive bacteria including multidrug resistant (MDR) phenotypes. Methods The broth microdilution method was used to determine the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of the above samples; column chromatography was used for the fractionation and purification of the leaves extract whilst the chemical structures of compounds were determined using spectroscopic techniques. Results Phytochemical investigation lead to the isolation of a mixture (1:3) of stigmasterol andβ -sitosterol (1 + 2 ), euphol (3 ), sitosterol-O-β- D - xylopyranoside (4 ), 3, 3′, 4′-tri-O- methylellagic acid (5 ), a mixture (1:1) of afzelin and quercetin-3-O-β -D -xylopyranoside (6 + 7 ), 3, 3′, 4′-tri-O -methylellagic acid 4-O-β -D -glucopyranoside (8 ), ellagic acid-4-O-β -xylopyranoside-3, 3′, 4′-trimethyl ether (9 ) from EDLc. Crude extract and fractions displayed selective activities with MIC values ranged from 32 to 1024 μg/mL for EDL against 84.9% of the 33 tested bacteria, 93.9% for EDLc, 69.7% for EDLb, 33.4% for EDLa and 0.03% for EDLd. MIC values ranged from 16 to 1024 μg/mL were obtained with EDLc3 and EDLc4 on all tested bacteria meanwhile other sub-fractions displayed selective activities. MIC value of 32 μg/mL was obtained with fractions EDLa againstEscherichia coli AG100, EDLc againstEnterobacer aerogenes ATCC13048 and EA298. For sub-fractions obtained from EDLc, the lowest MIC value of 16 μg/mL was recorded with EDLc3 againstStaphylococcus aureus MRSA11. A corresponding value of 8 μg/mL againstProvidencia stuartii NAE16 was recorded with EDLc33 obtained from further fractionation of EDLc3. EDLc3 had MIC values below 100 μg/mL against all tested bacteria. Compound5 as well as the mixture (1:1) of6 and7 inhibited the growth of all the tested bacteria with MICs ranged from 64 to 256 μg/mL. Conclusion Elaeophorbia drupifera is a potential source of phytomedicine to tackle MDR bacteria. Sub-fraction EDLc3 was more active than all isolated compounds and deserves further investigations to develop natural drug to combat Gram-negative, Gram-positive bacteria and otherwise MDR phenotypes.